Structuring the complexity of integrated landscape approaches into selectable, scalable, and measurable attributes - Waeber, Patrick O.; Carmenta, Rachel; Estrada Carmona, Natalia; Garcia, Claude A.; Falk, Thomas; Fellay, Abigail; Ghazoul, Jaboury; Reed, James; Willemen, Louise; Zhang, Wei; Kleinschroth, Fritz (Elsevier, 2023)
Integrated landscape approaches (ILA) aim to reconcile multiple, often competing, interests across agriculture, nature conservation, and other land uses. Recognized ILA design principles provide guidance for implementation, yet application remains challenging, and a strong performance evidence-base is yet to be formed. Through a critical literature review and focus group discussions with practitioners, we identified considerable diversity of ILA in actors, temporal, and spatial scales, inter alia. This diversity hampers learning from and steering ILA because of the intractable nature of the concept. Therefore, we developed a tool—an ‘ILA mixing board’—to structure the complexity of ILA into selectable and scalable attributes in a replicable way to allow planning, diagnosing, and comparing ILA. The ILA mixing board tool presents seven qualifiers, each representing a key attribute of ILA design and performance (for example, project flexibility, inclusiveness of the dialogue, and the centrality of the power distribution). Each qualifier has five (non-normative) outcome indicators that can be registered as present or absent. This process in turn guides planners, evaluators and other participating stakeholders involved in landscape management to diagnose the ILA type, or its performance. We apply the ILA mixing board to three ILA cases in Nicaragua, Madagascar, and the Congo Basin to show some of the many possible configurations of qualifiers on the mixing board. Further application of the tool would allow comparative analysis of the complexity of ILA in a structured and manageable way thereby enhancing the understanding of ILA performance and informing the development of evidence-based land use policy.